Bone micro-architecture of elite alpine skiers is not reflected by bone mineral density - Liphardt, Anna-Maria; Schipilow, J. D.; Macdonald, H. M.; Kan, M.; Zieger, A.; Boyd, S. K. (Osteoporosis international, 2015)
Bone quality is affected by muscle forces and external forces. We investigated how micro-architecture is influenced in elite alpine skiers who have received high loading levels throughout their adolescent bone development. Bone strength was higher in skiers, likely due to external forces, but muscle forces may also be a significant contributor.Impact loading and muscle forces affect bone quality, but little is known about how they influence 3 dimensional aspects of bone structure. This study investigated bone quality in female and male elite alpine skiers using high-resolution peripheral quantitative computed tomography (HR-pQCT).HR-pQCT at the distal radius and tibia, whole-body lean mass, and muscle strength were assessed in 10 female (22.7 ± 3.9 years) and 12 male (25.5 ± 3.3 years) Canadian national alpine team athletes and compared to recreationally active female (N = 10, 23.8 ± 3.2 years) and male (N = 12; 23.7 ± 3.6 years) control subjects. HR-pQCT standard parameters and customized cortical and finite element (FE) analyses were performed and analyzed using one-way ANOVA and Pearson's correlation.Male and female skiers had stronger bones than controls at radius (38-49 %, p < 0.001) and tibia (24-28 %, p < 0.001). This result was not consistently reflected by total bone mineral density (BMD) because higher trabecular BMD occurred in parallel with lower cortical BMD, which was due to a redistribution of mineral leading to a shift of the endocortical margin toward a thicker cortex. The endocortical regional adaptation was likely responsible for the greater strength of the athletes' bones. Lean mass and muscle strength was 29 to 90 % greater (p < 0.001) in athletes compared to controls. Good associations between muscle strength and FE-estimated bone strength were found (r = 0.63 to 0.80; p < 0.001), although micro-architecture was more strongly associated with muscle outcomes in females than males.Higher bone strength in elite alpine skiers is achieved through micro-architectural adaptation that is not apparent by BMD measurements alone. The improved micro-architecture at radius and tibia suggests that muscle forces may play an important role in bone adaptation.
EVALuna2:13501